Peran Bu Nyai Pesantren dalam Pelestarian Bahasa Madura sebagai Kearifan Lokal: Sebuah Analisis Fenomenologis - Romayyizah; Mohammad Rosi; Imamul Muttakin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The study of language has become a significant concern among academics, as language functions not only as a means of communication but also as a form of local wisdom that must be preserved to prevent extinction in the face of changing times. In this context, Islamic boarding schools (pesantren) play a strategic role as institutions that maintain and preserve the Madurese language through educational traditions and exemplary practices. The roles of kiai and nyai, particularly Madurese nyai, are central to shaping students’ character through the use of refined Madurese language (bhasa alos). This study aims to describe the role of pesantren and the figure of nyai in preserving local linguistic wisdom. The research employs a descriptive qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation of learning practices and daily interactions within the pesantren. The findings reveal that (1) the Madurese language possesses an elegant and rich literary structure; (2) Madurese nyai play a crucial role in instilling the use of refined Madurese (engghi-bhunten) among students and the surrounding community; and (3) the tradition of studying classical Islamic texts in pesantren consistently utilizes Madurese translations as a form of local wisdom preservation